Legal regulation in the field of citizens’ rights of access to environmental information in the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2018)
The article discusses the current state of the legal regulation in the sphere of ensuring citizens’ rights of access to environmental information in the Republic of Kazakhstan.Public awareness contributes to a better understanding of environmental issues and their direct participation in the decision. Public authorities should ensure appropriate public access to environmental information, as well as to take measures to improve the quality, timeliness and relevance of the material submitted. Key words: environmental information, convention, access to environmental information, environment, human rights.